The migrant wealth gap at the household level: Evidence from RIF regressions for Austria - Mattias Muckenhuber; Miriam Rehm; Matthias Schnetzer (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2021)
We investigate how previous generations of migrants and their children integrated into Austrian society, as measured by their wealth ownership. Using data from the Household Finance and Consumption Survey (HFCS), we document a positive average migrant wealth gap between migrant and native households. However, the raw gap is almost negligible for second generation migrant households, whereas it rises across the unconditional net wealth distribution for first generation migrant households and peaks at more than e140,000 around the 75th percentile. Decomposing the partial effects of a set of covariates using RIF regressions suggests that the lack of inheritances and the presence of children have the highest explanatory power for the migrant wealth gap of first generation migrant household. For second generation migrant households, inheritances have the highest impact, but they contribute negatively towards the explanation of the migrant wealth gap. In general, the covariates in our analysis can explain only a small part of the migrant wealth gap. Given the similarity of native and second generation migrant households, we cannot reject the hypothesis that migrants in the past integrated into Austrian society by acquiring comparable wealth levels.
Keywords: C31; D31; F22; G51; J15; J61; 330; Migration; Wealth Distribution; Wealth Gap; Unconditional Quantile Regression